Highlander Folk School and the industrial labor movement: Using the FBI files to develop a third perspective - Jeff Zacharakis-Jutz (Adult Education Research Conference, 1993)
This research analyzes the potential of using the main case FBI files as a primary source in reconstructing the history of Highlander Folk School between the early 1930s and the mid-1950s when the school was most active in the labor movement.